Updates from the International League Against Epilepsy Classification of Epilepsy (2017) and Focal Cortical Dysplasias (2022): Imaging Phenotype and Genetic Characterization - Agarwal, Amit; Bathla, Girish; Soni, Neetu; Desai, Amit; Middlebrooks, Erik; Patel, Vishal; Gupta, Vivek; Vibhute, Prasanna (American Journal of Neuroradiology, 2024)
The International League Against Epilepsy (ILAE) is an organization of 120 national chapters providing the most widely accepted and updated guidelines on epilepsy. In 2022, the ILAE Task Force revised the prior (2011) classification of focal cortical dysplasias to incorporate and update clinicopathologic and genetic information, with the aim to provide an objective classification scheme. New molecular-genetic information has led to the concept of “integrated diagnosis” on the same lines as brain tumors, with a multilayered diagnostic model providing a phenotype-genotype integration. Major changes in the new update were made to type II focal cortical dysplasias, apart from identification of new entities, such as mild malformations of cortical development and cortical malformation with oligodendroglial hyperplasia. No major changes were made to type I and III focal cortical dysplasias, given the lack of significant new genetic information. This review provides the latest update on changes to the classification of focal cortical dysplasias with discussion about the new entities. The ILAE in 2017 updated the classification of seizure and epilepsy with 3 levels of diagnosis, including seizure type, epilepsy type, and epilepsy syndrome, which are also briefly discussed here.BOSbottom of the sulcusEDGEedge-enhancing gradient-echoEEGelectroencephalographyFCDfocal cortical dysplasiaILAEInternational League Against EpilepsyMAP2microtubule-associated protein 2MEGmagnetoencephalographyMCDmalformations of cortical developmentmMCDmild malformations of cortical developmentMOGHEmalformation with oligodendroglial hyperplasiamTORmechanistic target of rapamycinNeuNneuronal nuclear protein